(untitled) (Al-Qamar, 2022)
Qur’an is the Apex authority of guidance for the Muslims and its teachings leads to have a peaceful life in a just, truthful, unbiased society having equity and fairness. Qur’an has given the clear orders that conduct of Rasool Allah (peace be upon him) is the ideal and best example to follow which is Sunnah. In spite of this ground realities reflect an erosion of our moral and ethical standards, an overall degradation of our value system, discord, rivalry and internal strife due to the sectarian differences. Although these differences are not about basic and fundamental beliefs but conflict over trivial matters is causing divisions into sects and further sub sects. This division and conflicts, once, at low scale and limited are now aggravated to such a sad state of affairs that Ulema of one faction are not prepared to interact or even sit with the Ulema of another faction. This rot has spread into various factions of the once homogeneous social sect. For finding the root causes of differences within Muslim Sunni sect along with Qur’an and Sunnah views over these differences, a research study has recently been conducted. The major findings indicate that majority of respondents could not base their arguments on Qur’an and Sunnah for their differences with other sub-sects. religious clerics are misleading their followers with hate speeches and objectionable printed material for their political and economic gains. However, it is imperative that our Ulema should forego the minor differences and endeavor sincerely to foster both inter-Communal and intra-communal harmony for the sake of peaceful co-existence and societal progress, which is the need of the hour.